Concept and Implementation of Islamic Character Education in Educational Institutions - Muh. Alif Kurniawan; Fadhlurrahman Fadhlurrahman; Zalik Nuryana (Universitas Ahmad Dahlan, 2022)
Education institutions must implement Islamic character education on a massive scale immediately. This study aims to describe the concept and implementation of character education in educational institutions to address student association issues without delay. This investigation is library-based (library research). The obtained data were then analyzed with a hermeneutic approach through content analysis. This study concludes that the concept of character education has been taught in Islam for quite some time. The verses of the Qur'an and hadith explain this. Similar to Surah Luqman verses 17 and 18, as well as the hadith narrated by Imam Bukhari and Muslims from the path of Abdullah bin Amr bin Ash's companions. Implementing Islamic character education in educational institutions can be categorized initially by age range, from early childhood to adolescence. To evaluate the success of Islamic character education in specific educational institutions, class-based, school-based, and community-based Islamic character education must be implemented. The implication for educational institutions is a greater emphasis on Islamic character education beginning at a young age so that students develop Islamic character. This study contributes to advancing and implementing Islamic character education in educational institutions.